Omega-3 Fatty Acids and Vitamin D in Cardiology - Norbert Güttler; Kirila Zheleva; Mariana Parahuleva; Ridvan Chasan; Mehmet Bilgin; Christiane Neuhof; Mehmet Burgazli; Bernd Niemann; Ali Erdogan; Andreas Böning (Cardiology Research and Practice)
Dietary modification and supplementation play an increasingly important role in the conservative treatment of cardiovascular disease. Current interest has focused on n-3 polyunsaturated fatty acids (PUFA) and vitamin D. Clinical trial results on this subject are contradictory in many aspects. Several studies indicate that n-3 PUFA consumption improves vascular and cardiac hemodynamics, triglycerides, and possibly endothelial function, autonomic control, inflammation, thrombosis, and arrhythmia. Experimental studies show effects on membrane structure and associated functions, ion channel properties, genetic regulation, and production of anti-inflammatory mediators. Clinical trials evaluating a possible reduction in cardiovascular disease by n-3 PUFA have shown different results. Supplementation of vitamin D is common regarding prevention and treatment of osteoporosis. But vitamin D also seems to have several effects on the cardiovascular system. Vitamin D deficiency appears to be related to an increase in parathyroid hormone levels and can predispose to essential hypertension and left ventricular hypertrophy, increased insulin resistance, and eventually to atherosclerosis and adverse cardiovascular events. Randomized prospective clinical trials are needed to determine whether vitamin D and omega-3 FA supplementation therapy should be recommended as a routine therapy for primary or secondary prevention of cardiovascular disease.